Identification and morphology of two polycentropodid caddisfly larvae from the Cevennes and the French and Italian Alps: Plectrocnemia cevennensis Coppa 2011 and Plectrocnemia praestans McLachlan 1884 - Waringer, Johann; Coppa, Gennaro (Zootaxa, 2021)
The collection of adults, mature male pupae, and the absence of confusing species at the sampling sites located in the Cevennes and French Alps enabled descriptions of the hitherto unknown larvae of Plectrocnemia cevennensis Coppa 2011 and P. praestans McLachlan 1884 (Trichoptera, Polycentropodidae). We present information on the morphology of the larvae and illustrate the most important diagnostic features. In the context of the larval key to European Plectrocnemia species by Waringer & Graf (2020), P. cevennensis keys together with P. scruposa McLachlan 1880, whereas P. praestans keys with P. conspersa (Curtis 1834). These two species pairs are morphologically very close; P. cevennensis and P. scruposa can be separated by the numbers of secondary setae on the last abdominal sternum, but the separation of P. praestans and P. conspersa is not always possible.